1992
DOI: 10.1021/bi00145a018
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman study on the active-site structure of a cooperative hemerythrin

Abstract: Resonance Raman spectra were observed for the oxy and azidomet forms of a cooperative hemerythrin (Hr) isolated from Lingula unguis and a noncooperative Hr from Siphonosoma cumanense. The O-O stretching frequency of the oxy derivative of the L. unguis Hr was lower in the high-affinity form generated at pH 7.6 than in the low-affinity form generated at pH 6.2, while that of the S. cumanense Hr did not change at those two pH values. The Fe-O-Fe symmetric stretching mode of L. unguis azidomet-Hr exhibited a frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…This interaction would lead to the stabilization of a dioxygen adduct . Interestingly, the experimental evidence in favor of a hydrogen bonding between coordinated O 2 and an amino acid side chain also supports the proposal of this type of H-bonding being responsible for the allosteric effects and cooperativity in hemerythrin from Lingula unguis (a rare example of cooperative octameric hemerythrins). , …”
Section: 21 Reactions With O2supporting
confidence: 64%
See 1 more Smart Citation
“…This interaction would lead to the stabilization of a dioxygen adduct . Interestingly, the experimental evidence in favor of a hydrogen bonding between coordinated O 2 and an amino acid side chain also supports the proposal of this type of H-bonding being responsible for the allosteric effects and cooperativity in hemerythrin from Lingula unguis (a rare example of cooperative octameric hemerythrins). , …”
Section: 21 Reactions With O2supporting
confidence: 64%
“…110 Interestingly, the experimental evidence in favor of a hydrogen bonding between coordinated O 2 and an amino acid side chain also supports the proposal of this type of H-bonding being responsible for the allosteric effects and cooperativity in hemerythrin from Lingula unguis (a rare example of cooperative octameric hemerythrins). 21,111 As mentioned above, leucine mutations have a profound effect on the oxyHr autoxidation rates. With the sole exception of L98Y, which is stabilized by a hydrogen bond to a coordinated O 2 , hemerythrin mutants are far more susceptible to autoxidation than the wild-type proteins.…”
Section: Reactions With Omentioning
confidence: 92%
“…Two brachiopod Hrs (Manwell, 1960;Richardson et al, 1983;Zhang & Kurtz, 1991) consist of R 4 β 4 octamers that display cooperative oxygen uptake. A resonance Raman study (Kaminaka et al, 1992) of one of these noted a pHdependent shift of the ν O-O stretch of the oxy form. This was interpreted in terms of a hydrogen-bonding interaction, between bound dioxygen and an unidentified amino acid, that acts to stabilize the higher-affinity oxy structure.…”
Section: Discussionmentioning
confidence: 99%
“…When the resonance Raman spectrum of oxyHr in D 2 O was compared to that in H 2 O, an upshift of 2−4 cm -1 in the O−O stretching frequency was obtained. , This result was interpreted as proof that the bound peroxide in oxyHr is protonated, since the O−O stretching frequency of a terminally bound hydroperoxide group should be sensitive to isotopic substitution of deuterium for hydrogen. When 3 was generated by using a mixture of 1:1 H 2 O 2 /D 2 O 2 (25% in 1:1 H 2 O/D 2 O), the resonance Raman spectrum showed a broader band at 870 cm -1 , as indicated in Figure .…”
Section: Resultsmentioning
confidence: 98%
“…Shifts of 2−4 cm -1 in the O−O stretching frequency of oxyHr occurred when the resonance Raman spectrum was recorded in D 2 O, , which was taken as support for protonation of the peroxide ligand. Resonance Raman studies of the symmetric Fe−O−Fe vibration in various forms of hemerythrin revealed a perturbation in the Fe−O stretch, suggesting the existence of the hydrogen bond from the terminal hydroperoxide to the bridging oxide. ,, The presence of such a putative hydrogen bond between the hydroperoxide and the bridging oxide in oxyHr has not yet been encountered in synthetic model compounds, nor has a functional model that binds O 2 reversibly like the protein been obtained.…”
Section: Introductionmentioning
confidence: 98%